Scaffolding Technique to overcome Students' Mathematics Learning Anxiety - Intan Nadilah; Andika Setyo Budi Lestari (FKIP Universitas Halu Oleo, 2023)
Mathematics is a subject at school that is in-depth and very important in the world of education. However, Mathematics is often used by students as Mathematics Anxiety. This is often associated with fear and lack of confidence in Mathematics. So an alternative is needed as a solution, which can be tried using the Scaffolding Technique with a combination of Social Arithmetic material. The aim of this research is to evaluate the extent to which the application of scaffolding techniques can increase the effectiveness of overcoming students' mathematics anxiety in understanding Social Arithmetic material. This type of research is PTK with a focus on learning strategies in the classroom. Direct assessment techniques with notes using observation guides and field notes to summarize everything that happened. In an ongoing program, it is necessary to achieve 75-100% of the set goals in order to be considered successful. From the research results, it can be confirmed that there has been an increase in both the average value and percentage, indicating that the research objectives have achieved the expected level of effectiveness. This improvement is measured by looking at the results of student learning scores, where a score of ≥75 or >75 is considered an indicator of significant improvement. The use of the Scaffolding Technique in Social Arithmetic material, through the use of Games, is a prominent factor in achieving positive results. So, it can be concluded that the application of the Scaffolding Technique strategy is able to increase students' understanding of Social Arithmetic material.